PEDIATRIC HELMINTHIASIS AND THEIR INDICATIONS (ON THE EXAMPLE OF SURKHANDARYA REGION) - Djuraeva Muhabbat Ergashovna; Almardonova Zulxumor Jalilovna (Scholar Express Journals, 2021)
This article presents information and conclusions about helminths in children in Surkhandarya region of Uzbekistan. According to the research results, in Surkhandarya province 44% of children are infected with enterobiasis and 23% with ascariasis, and the reasons for this are explained
Keywords: Healthy lifestyle; pathogens weaken; children's helminthosis; children's disability